2006
DOI: 10.1210/jc.2005-1017
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Studies of Recombinant Human Insulin-Like Growth Factor I (rhIGF-I)/rhIGF-Binding Protein-3 Complex Administered to Patients with Growth Hormone Insensitivity Syndrome

Abstract: These data demonstrated that the rhIGF-I/rhIGFBP-3 complex was effective in increasing levels of circulating total and free IGF-I into the normal range for a 24-h period after a single sc administration in patients with GHIS, and that administration of rhIGF-I/rhIGFBP-3 was safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…Less clear, however, is the specific effect(s) of the STAT5b mutations on immune function(s), although recurring pulmonary infections appear to be a common consequence. Finally, while GH therapy to correct the poor linear growth would be predicted to be ineffective for these patients, it is possible that treatment with IGF-I or IGF-I/IGFBP-3 complex would be of clinical value, as has been demonstrated for patients with other forms of primary IGF deficiency [19,20,21,22,23], and is currently under consideration for the present subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Less clear, however, is the specific effect(s) of the STAT5b mutations on immune function(s), although recurring pulmonary infections appear to be a common consequence. Finally, while GH therapy to correct the poor linear growth would be predicted to be ineffective for these patients, it is possible that treatment with IGF-I or IGF-I/IGFBP-3 complex would be of clinical value, as has been demonstrated for patients with other forms of primary IGF deficiency [19,20,21,22,23], and is currently under consideration for the present subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pharmacological studies of an IGF-I compound containing a 1:1 molar complex of rhIGF-I and rhIGFBP-3 (IGF-binding protein; Insmed, Inc., Glen Allen, Va., USA) demonstrated that the complex was effective in increasing levels of circulating total and free IGF-I and that the administration in patients with GHIS should be safe and well-tolerated [4]. In addition, it was even hypothesized that this complex mimics the physiological effects of IGF-I with a more favorable pharmacokinetic profile [4]. …”
Section: Introductionmentioning
confidence: 99%
“…37 Preliminary uncontrolled studies, on treatment of IGFD with the complexes of IGF1/IGFBP-3 (mecasermin rinfabate), showed extension of serum IGF-1 half life and normalization of serum levels of IGF1, but failed to demonstrate an improvement in growth rate, compared to treatment with rhIGF1 alone. 17,34 Unpublished data 35 demonstrated that patients receiving rhIGF1/IGFBP-3 at a dose equivalent to a daily dose of rhIGF1 of 200 µg/kg showed an increase in height velocity only of 3 cm/year. Patients treated with higher dose of the complex comparable to 400 µg/kg of rhIGF1 per day showed an increment in growth rate of 6.3 cm/year.…”
Section: Dovepressmentioning
confidence: 99%
“…The 24 hour area under the curve (AUC) was comparable between rhIGF1 therapy and the higher combination dose, while it was less for the lower combination dose. 34 The comparable levels of circulating IGF-1 either in patients treated with rhIGF1 alone or with the complex, may be explained by the possible binding of IGF-1 to other IGFBPs. Indeed, IGFBP-2 is elevated in IGFD patients and increases with rhIGF1 therapy.…”
Section: Dovepressmentioning
confidence: 99%